Rhizobial Chemoattractants, the Taste and Preferences of Legume Symbionts - Compton, K. Karl; Scharf, Birgit E. (Frontiers in Plant Science, 2021)
The development of host-microbe interactions between legumes and their cognate rhizobia requires localization of the bacteria to productive sites of initiation on the plant roots. This end is achieved by the motility apparatus that propels the bacterium and the chemotaxis system that guides it. Motility and chemotaxis aid rhizobia in their competitiveness for space, resources, and nodulation opportunities. Here, we examine studies on chemotaxis of three major model rhizobia, namely Sinorhizobium meliloti, Rhizobium leguminosarum, and Bradyrhizobium japonicum, cataloging their range of attractant molecules and correlating this in the context of root and seed exudate compositions. Current research areas will be summarized, gaps in knowledge discussed, and future directions described.